Population monitoring of language and cognitive development in Australia: The Australian Early Development Index - Brinkman, Sally; Sayers, M.; Goldfeld, S.; Kline, J. (Informa UK Ltd, 2009)
Username: Password: Search: Advanced searchHome Journals View All Journals Expert Opinion on Biological Therapy Drug Delivery Drug Discovery Drug Metabolism & Toxicology Drug Safety Emerging Drugs Investigational Drugs Medical Diagnostics Pharmacotherapy Therapeutic Patents Therapeutic Targets Current Medical Research and Opinion Journal of Medical Economics Resources For Authors For Readers For Librarians For Consortia For Advertisers Services Alerting Services Manuscript Submission Publishing Services Reprints Drug evaluations Advertising Supplements Foreign Rights/Translations Contacts About Us Contacts Jobs SummaryInternational Journal of Speech-Language Pathology2009, Vol. 11, No. 5, Pages 419-430 , DOI 10.1080/17549500903147552 Population monitoring of language and cognitive development in Australia: The Australian Early Development IndexSally Brinkman?1,2,3*, Mary Sayers?4,5, Sharon Goldfeld?4,5, Jodie Kline?4,51Curtin Health Innovation Research Institute, Curtin University of Technology, Perth, Australia2Telethon Institute for Child Health Research, Perth, Australia3Australian Institute for Social Research, University of Adelaide4Murdoch Childrens Research Institute, Royal Children's Hospital, Melbourne, Australia5The University of Melbourne, Australia*Correspondence: Sally Brinkman, Curtin University – Centre for Developmental Health, Institute for Child Health Research, PO Box 855, West Perth, WA, 6872, Australia +61 8-9489-7714 sallyb@ichr.uwa.edu.auThe Australian Early Development Index (AEDI) is a population measure of child development. The AEDI measures Language and Cognitive Development, Social Competence, Emotional Maturity, Physical Health and Wellbeing, and Communication Skills and General Knowledge. In Australia these data are collected by teachers for children in their first full time year of schooling. The aim of this paper is to aid people's understanding and interpretation of population measures such as the AEDI. With a greater awareness of the merits and complexities of population data clinicians and allied health professionals can play a vital role in aiding communities and policy makers to interpret and act upon the data in an intelligent way. This paper is primarily descriptive providing background information on the development and use of the instrument utilizing one of the 5 developmental domains (Language and Cognitive Development) as an example. The results show a complex relationship between children residing in differing socio-economic regions, children with English as their primary or secondary language and children who are able or not able to effectively communicate in English.Full Text | PDF (134 KB) | PDF Plus (135 KB) Forward Links to Citing ArticlesCatherine L. Taylor, Stephen R. Zubrick. (2009) Predicting children's speech, language and reading impairment over time. International Journal of Speech-Language Pathology 11:5, 341-343Online publication date: 1-Jan-2009.Summary | Full Text | PDF (59 KB) | PDF Plus (59 KB) --------------------------------------------------------------------------------Users who read this article also read: Predicting children's speech, language and reading impairment over timeCatherine L. Taylor, Stephen R. ZubrickInternational Journal of Speech-Language Pathology, Jan 2009, Vol. 11, No. 5, Pages 341-343. Username: Password: Search: Advanced searchHome Journals View All Journals Expert Opinion on Biological Therapy Drug Delivery Drug Discovery Drug Metabolism & Toxicology Drug Safety Emerging Drugs Investigational Drugs Medical Diagnostics Pharmacotherapy Therapeutic Patents Therapeutic Targets Current Medical Research and Opinion Journal of Medical Economics Resources For Authors For Readers For Librarians For Consortia For Advertisers Services Alerting Services Manuscript Submission Publishing Services Reprints Drug evaluations Advertising Supplements Foreign Rights/Translations Contacts About Us Contacts Jobs SummaryInternational Journal of Speech-Language Pathology2009, Vol. 11, No. 5, Pages 419-430 , DOI 10.1080/17549500903147552 Population monitoring of language and cognitive development in Australia: The Australian Early Development IndexSally Brinkman?1,2,3*, Mary Sayers?4,5, Sharon Goldfeld?4,5, Jodie Kline?4,51Curtin Health Innovation Research Institute, Curtin University of Technology, Perth, Australia2Telethon Institute for Child Health Research, Perth, Australia3Australian Institute for Social Research, University of Adelaide4Murdoch Childrens Research Institute, Royal Children's Hospital, Melbourne, Australia5The University of Melbourne, Australia*Correspondence: Sally Brinkman, Curtin University – Centre for Developmental Health, Institute for Child Health Research, PO Box 855, West Perth, WA, 6872, Australia +61 8-9489-7714 sallyb@ichr.uwa.edu.auThe Australian Early Development Index (AEDI) is a population measure of child development. The AEDI measures Language and Cognitive Development, Social Competence, Emotional Maturity, Physical Health and Wellbeing, and Communication Skills and General Knowledge. In Australia these data are collected by teachers for children in their first full time year of schooling. The aim of this paper is to aid people's understanding and interpretation of population measures such as the AEDI. With a greater awareness of the merits and complexities of population data clinicians and allied health professionals can play a vital role in aiding communities and policy makers to interpret and act upon the data in an intelligent way. This paper is primarily descriptive providing background information on the development and use of the instrument utilizing one of the 5 developmental domains (Language and Cognitive Development) as an example. The results show a complex relationship between children residing in differing socio-economic regions, children with English as their primary or secondary language and children who are able or not able to effectively communicate in English.Full Text | PDF (134 KB) | PDF Plus (135 KB) Forward Links to Citing ArticlesCatherine L. Taylor, Stephen R. Zubrick. (2009) Predicting children's speech, language and reading impairment over time. International Journal of Speech-Language Pathology 11:5, 341-343Online publication date: 1-Jan-2009.Summary | Full Text | PDF (59 KB) | PDF Plus (59 KB) --------------------------------------------------------------------------------Users who read this article also read: Predicting children's speech, language and reading impairment over timeCatherine L. Taylor, Stephen R. ZubrickInternational Journal of Speech-Language Pathology, Jan 2009, Vol. 11, No. 5, Pages 341-343.